Rhizoctonia solani AG-1 IA infects both rice and signalgrass in the Colombian Llanos - Ramos-molina, Lina Maria; Chavarro-mesa, Edisson; Pereira, Danilo Augusto Dos Santos; Silva-herrera, María Del Rosario; Ceresini, Paulo Cezar (Escola de Agronomia/UFG, 2016)
ABSTRACT Foliar blight and death of signalgrass (Urochloa spp.) pastures are caused by the Rhizoctonia solani fungus. This study aimed at determining which pathogens from the Rhizoctonia species complex are associated with leaf and sheath blight in Urochloa and rice, in the Colombian Llanos. Sympatric areas of Urochloa pastures adjacent to rice cropping areas were sampled using a linear transect system. The pathogens were identified using morphological traits, molecular detection based on specific primers and sequencing of the ITS-5.8S rDNA region. R. solani AG-1 IA predominated as the pathogen associated with foliar blight in all samples from U. brizantha cv. 'Toledo' and hybrid Urochloa cv. 'Mulato'. Besides R. solani AG-1 IA (18 % of the samples), Rhizoctonia oryzae-sativae (71 %) and Sclerotium hydrophilum (11 %) were also detected. In the cross-pathogenicity test, the R. solani AG-1 IA fungus was the most aggressive to Urochloa, while R. oryzae-sativae produced very mild infection symptoms. This is the first report of R. oryzae-sativae and S. hydrophilum associated with the complex of rice sheath blight diseases in Colombia.

RESUMO A queima da folha e morte de pastagens do gênero Urochloa são causadas pelo fungo Rhizoctonia solani. Objetivou-se determinar que patógenos do complexo de espécies do gênero Rhizoctonia estão associados à queima da folha e bainha em Urochloa e arroz, nos Llanos Colombianos. Utilizando-se o sistema de transcetos lineares, foram amostradas áreas de pastagens de Urochloa simpátricas, adjacentes às de arroz. A identificação dos patógenos foi efetuada por caracterização morfológica, detecção molecular baseada em iniciadores específicos e sequenciamento da região ITS-5,8S do rDNA. R. solani AG-1 IA predominou como patógeno associado à queima da folha em todas as amostras de U. brizantha cv. 'Toledo' e híbrido Urochloa cv. 'Mulato'. Além de R. solani AG-1 IA (18 % das amostras), R. oryzae-sativae (71 %) e Sclerotium hydrophilum (11 %) também foram detectados. No teste de patogenicidade, o fungo R. solani AG-1 IA foi o mais agressivo a Urochloa, enquanto R. oryzae-sativae ocasionou sintomas muito leves de infecção. Este é o primeiro relato de que os fungos R. oryzae-sativae e S. hydrophilum estão associados ao complexo de doenças da bainha do arroz, na Colômbia.
Rhizoctonia solani AG-1 IA infecta arroz e braquiária nos Llanos Colombianos
Keywords: Urochloa spp.; Rhizoctonia oryzae-sativae; Sclerotium hydrophilum; Urochloa spp.; Rhizoctonia oryzaesativae; Sclerotium hydrophilum